SURVIVAL MARKETING STRATEGY DI ERA NEW WAVE - Heng, Lie (MABIS, 2012)
Marketing Experts have stated many marketing theories and concepts in order to help us to understand what and how, as well as how important marketing is for a company in achieving its goal. Marketing terms such as environmental analysis, segmentation, targeting, positioning, differentiation, marketing mix, selling, brand, service, process and the like (etc) have become very familiar for us. However, event though it is easy to search for literature on marketing theory and concept nowadays as we needed them, sometimes, the information we obtain is not as whole, it is as broken as in to pieces, making it hard to comprehend. This paper aims at giving a solid and directed illustration on marketing main elements in todayâs world. Changes in market landscape which is full of turbulence, do not threat marketing as a function in a company anymore instead, marketing has developed into more strategic way.